Response of Three Miscanthus × giganteus Cultivars to Toxic Elements Stress: Part 1, Plant Defence Mechanisms - Karim Suhail Al Souki; Clarisse Liné; Francis Douay; Bertrand Pourrut (Plants, 2021)
Miscanthus × giganteus demonstrated good phytostabilization potentials in toxic element (TE) contaminated soils. However, information about its tolerance to elevated concentrations is still scarce. Therefore, an ex-situ pot experiment was launched using three cultivars (termed B, U, and A) grown in soils with a gradient Cd, Pb and Zn concentrations. Control plants were also cultivated in non-contaminated soil. Results show that the number of tillers per plant, stem diameter as well as leaf photosynthetic pigments (chlorophyll a, b and carotenoids) were negatively impacted by soil contamination. On the other hand, phenolic compounds, flavonoids, tannins, and anthocyanins levels along with the antioxidant enzymatic activities of superoxide dismutase, ascorbate peroxidase and glutathione reductase increased in the plants grown on contaminated soils. Altogether, these data demonstrate that miscanthus is impacted by concentrations of toxic elements yet is able to tolerate high levels of soil contamination. These results may contribute to clarifying the miscanthus tolerance strategy against high contamination levels and its efficiency in phytoremediation.